Proteomic signatures of in vivo muscle oxidative capacity in healthy adults. Issue 4 (20th March 2020) - Adelnia, Fatemeh; Ubaida‐Mohien, Ceereena; Moaddel, Ruin; Shardell, Michelle; Lyashkov, Alexey; Fishbein, Kenneth W.; Aon, Miguel A.; Spencer, Richard G.; Ferrucci, Luigi
Abstract: Adequate support of energy for biological activities and during fluctuation of energetic demand is crucial for healthy aging; however, mechanisms for energy decline as well as compensatory mechanisms that counteract such decline remain unclear. We conducted a discovery proteomic study of skeletal muscle in 57 healthy adults (22 women and 35 men; aged 23–87 years) to identify proteins overrepresented and underrepresented with better muscle oxidative capacity, a robust measure of in vivo mitochondrial function, independent of age, sex, and physical activity. Muscle oxidative capacity was assessed by 31 P magnetic resonance spectroscopy postexercise phosphocreatine (PCr) recovery time (τPCr ) in the vastus lateralis muscle, with smaller τPCr values reflecting better oxidative capacity. Of the 4, 300 proteins quantified by LC‐MS in muscle biopsies, 253 were significantly overrepresented with better muscle oxidative capacity. Enrichment analysis revealed three major protein clusters: (a) proteins involved in key energetic mitochondrial functions especially complex I of the electron transport chain, tricarboxylic acid (TCA) cycle, fatty acid oxidation, and mitochondrial ABC transporters; (b) spliceosome proteins that regulate mRNA alternative splicing machinery, and (c) proteins involved in translation within mitochondria. Our findings suggest that alternative splicing and mechanisms that modulate mitochondrial protein synthesis are central features of the molecular mechanisms aimed at maintaining mitochondrial function in the face of impairment. Whether these mechanisms are compensatory attempt to counteract the effect of aging on mitochondrial function should be further tested in longitudinal studies. Abstract : The skeletal muscle proteins associated with in vivo muscle oxidative capacity, measured by phosphorous magnetic resonance spectroscopy ( 31 P MRS), were identified in a cohort of healthy adults. Functional annotation analysis revealed that, independent of age and physical activity, three major protein clusters were strongly associated with in vivo mitochondrial function, namely mRNA processing and splicing, respiratory electron transport chain, and mitochondrial protein translation.